IMPLEMENTASI PERNYATAAN STANDAR AKUNTANSI KEUANGAN NOMOR 109 TAHUN 2008 TENTANG AKUNTANSI ZAKAT DAN INFAQ/SEDEKAH PADA PENYUSUNAN LAPORAN KEUANGAN (STUDI PADA BADAN AMIL ZAKAT NASIONAL PROVINSI KALIMANTAN TIMUR) - Agustina Ningsih; Mursyid Mursyid; Dedy Mainata; Yovanda Noni (Borneo Islamic Finance and Economics Journal, 2021)
The amil zakat Agency is an institution that has the responsibilty (mandate) of the muzakki to distribute the zakat they have paid to people in need. As a trust holding institutions are required to record every zakat deposit from muzakki and report the zakat management to the public in a transparent and accountable manner in accordance with the Statement of Financial Accunting (PSAK) No. 109 concerning zakat and infaq/alms accounting. Therefore, this tudy aims to examine the pattern and application of zakat and infaq/alms accounting based on PSAK No. 109 at the National Zakat Agency (BAZNAS) of East Kalimantan Province.This type of research is field research is field research using a qualitative descriptive approach. The informants in this study were staff concerned in making the financial reports of BAZNAS East Kalimantan Province. Instruments in data collction used were observation, interviews and documentation. The stages in obtaining the dataused are data reduction, data presentation and drawing conclusions.The results showed that the pattern of preparing financial statements at BAZNAS East Kalimantan Province includes components of balnce reports (financial position reports), reports of change in funds, reports of changes in assets under managemnt, cash flow reports, and notes on financial statements that are in accordance with PSAK 109. Financial reports that are conducted 2 times a year, six months and at the end to the year. The financial statements that are presented are not only physical, but are presented through an application called SIMBA(BAZNAS Management Information System). Where in its application, the financial statements aopplied by the institution have reffered to and are in accordance with PSAK 109 concerning zakat adn infaq/alms accounting/